Nuclear medicine physics : the basics - Chandra, Ramesh, 1938- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2018)
Part of the renowned The Basics series, Nuclear Medicine Physics helps build foundational knowledge of how and why things happen in the clinical environment. Ideal for board review and reference, the 8th edition provides a practical summary of this complex field, focusing on essential details as well as real-life examples taken from nuclear medicine practice. New full-color illustrations, concise text, essential mathematical equations, key points, review questions, and useful appendices help you quickly master challenging concepts in nuclear medicine physics. Features: Two new chapters cover tomographic nuclear medicine imaging, and an all-new chapter discusses computer interfacing and image processing. Expanded coverage of Emission Computed Tomography is now presented in three separate chapters devoted to general principles, SPECT, and PET. Now includes a range of important PET radiotracers, as well as a timely discussion of theranostic uses of radiopharmaceuticals. New coauthor Dr. Arman Rahmim brings a fresh perspective and valuable knowledge and experience to this edition. An essential resource for radiology residents and practitioners, nuclear cardiologists, medical physicists, and radiologic technologists. Your book purchase includes a complimentary download of the enhanced eBook for iOS, Android, PC & Mac. Take advantage of these practical features that will improve your eBook experience: The ability to download the eBook on multiple devices at one time - providing a seamless reading experience online or offline Powerful search tools and smart navigation cross-links that allow you to search within this book, or across your entire library of VitalSource eBooks Multiple viewing options that enable you to scale images and text to any size without losing page clarity as well as responsive design The ability to highlight text and add notes with one click